Effective management of slums - case study of Kalaburagi city, Karnataka, India - Sulochana Shekhar (Journal of Urban Management, 2020)
As urbanization grows, we may expect that slums will tend to grow even faster. Kalaburagi is a second tier city and an important commercial hub for the Hyderabad-Karnataka region located in the north eastern part of Karnataka state. It attracts the rural folk from neighbouring districts and the city is undergoing rapid changes in terms of population growth as well as in the degree of urbanization due to which the slum population is increasing. There are 60 slums that account for 11% of city's population. This study aims to contribute some sustainable methodologies for better execution of slum development programs to advance the living conditions of slum dwellers. Slum ontology has been built to identify slums from very high-resolution satellite data that will benefit all stakeholders. The developed ontology was validated with field survey and the help of field photographs, the physical and socio-economic conditions were documented. As per the slum ontology, basic inputs for the Cellular Automata (CA) model were identified and criteria maps with scores were generated. The suitability map was created by giving appropriate weight to the factors. When the slum map prepared based on slum ontology was overlaid on the final results, the CA model output has given reliable results regarding current slum distribution and also a hint of the possible occurrence of slums in the future. Since the proposed land use plan for 2021 has been finalized by the Urban Local Body (ULB), the suitable area for developing affordable housing stock was suggested for preventing slums from arising. The Spatial Decision Support System (SDSS) was built for selecting slum development options. The design and running of the SDSS model were demonstrated with one case study - Borabai nagar slum to enable the ULB to apply the approach to other slum areas for effective implementation of slum development programs.
Keywords: 710